Levodopa-Induced Dyskinesia Is Related to Indirect Pathway Medium Spiny Neuron Excitotoxicity: A Hypothesis Based on an Unexpected Finding; Parkinson’s Disease; Vol. 2016 - Ivanova S. A. Svetlana Aleksandrovna (2016, 2016)
Title screen